Gaya Kepemimpinan Transformasional dan Lingkungan Kerja terhadap Organization Citizenship Behavior Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening pada Dinas Kesehatan Kabupaten Jember - Arvianto, Ronny; Ni Nyoman Putu Martini; Budi Santoso (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the influence of transformational leadership style, work environment, on Organizational Citizenship Behavior (OCB) with satisfaction as an intervention variable at the Jember District Health Office. The sample in this study was 118 respondents. The sampling technique used simple random sampling. Data collection was carried out by distributing questionnaires to all respondents. The data source used is a primary data source. The analysis method uses SEM PLS analysis with the WarpPLS 7.0 research tool. The results of the direct influence test showed that (1) transformational leadership and work environment variables directly have a positive effect on satisfaction but specifically for transformational leadership are not significant on satisfaction. (2) transformational leadership variables, work environment and satisfaction directly have a positive and significant effect on OCB. (3) transformational leadership variables indirectly have a positive but insignificant effect on OCB through satisfaction, but the work environment indirectly has a significant effect on OCB through satisfaction Keywords: Transformational Leadership, Work Environment, Satisfaction, Organizational Citizenship Behavior